Tet2 facilitates the de-repression of myeloid target genes during C/EBPa induced transdifferentiation of pre-B cells - Kallin, Eric M. (2012)
The methylcytosine hydroxylase Tet2 has been implicated in hematopoietic differentiation and the formation of myeloid malignancies when mutated. An ideal system to study the role of Tet2 in myelopoeisis is C/EBPa induced transdifferentiation of pre-B cells into macrophages. Here we found that C/EBPa binds to upstream regions of Tet2 and that the gene becomes activated. Tet2 knockdowns impaired the upregulation of macrophage markers as well as phagocytic capacity, suggesting that the enzyme is required for both early and late stage myeloid differentiation. A slightly weaker effect was seen in primary cells with a Tet2 ablation. Expression arrays of transdifferentiating cells with Tet2 knockdowns permitted the identification of a small subset of myeloid genes whose upregulation was blunted. Activation of these target genes was accompanied by rapid increases of promoter hydroxy-methylation. Our observations indicate that Tet2 helps C/EBPa rapidly de-repress myeloid genes during the conversion of pre-B cells into macrophages.